ANALISIS PERENCANAAN PEMBANGUNAN DESA (Studi Kasus Pada Desa Batu Rotok Kecamatan Batu Lanteh) - K Kamaruddin; I Nyoman Sutama; S Suhaima (Jurnal Ekonomi & Bisnis, 2021)
This study aims to determine development planning in Batu Rotok Village, Batulanteh District and the factors that influence development planning in Batu Rotok Village, Batulanteh District. This type of research is descriptive qualitative research. The number of informants is 8 informants. Data collection methods used in this study were questionnaires, interviews and documentation. The types of data used are qualitative data and quantitative data. The data analysis technique is using the theory of Miles and Huberman which consists of data collection, data reduction, data presentation and drawing conclusions. The results showed that the development planning process in Batu rotok Village, Batulanteh District had not shown an optimal increase in social welfare, this could be seen from the less than optimal ability of the village government apparatus in carrying out good development planning that was right on target in supervising development planning. The factors that influence the development planning of Batu Rotok Village are: the amount of costs, facilities and infrastructure, and implementation time.